Development of Animated Videos Based on the Merdeka Curriculum to Improve Students' Mathematical Problem Solving Ability - Dista Anggraeni Safitri; Hamidah Suryani Lukman; Aritsya Imswatama (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
This research aims to develop an animation video based on the merdeka curriculum to improve mathematical problem solving skills of elementary school students by testing its quality based on valid, practical, and effective criteria. This type of research is R&D with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were 1 teacher and 23 fifth grade students at one of the public elementary schools in Sukabumi City. The instruments used in the study were media expert and material expert validation sheets to test the validity of the animated video, teacher and student response questionnaires to test the practicality of the animated video, and student mathematical problem solving ability tests to test the effectiveness of the animated video. The data analysis techniques used were Hypothesis Test and N-Gain analysis. The results showed that (1) The animation video developed was included in the category of very valid or very feasible to be tested. (2) Teachers and students gave very good responses to the animated video developed and included in the very practical category. (3) Based on the results of hypothesis testing and N-Gain, it shows that there is an increase in students' mathematical problem solving skills in the medium category so that the animated video developed is declared effective.